The Role of Dormitory Management in Preventive Bullying Action at the Modern Darussalam Gontor Islamic Boarding School Campus 7, Kalianda - South Lampung - Rizky Cahya Pratama; Ahmad Luviadi; Muhammad Rizkal Fajri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article discusses the role of dormitory administrators in bullying preventive action at Pondok Modern Darussalam Gontor Campus 7, Kalianda - South Lampung. This research uses a qualitative approach with a focus on the Aligarh dormitory as a place for new santri to live. Dormitory administrators have a big challenge in preventing bullying because some students have a stubborn character and are difficult to accept direction. Efforts are needed to increase santri's understanding of the importance of respect and togetherness in order to create an inclusive dormitory environment. The research method involved interviews, observation, and documentation to collect data. The results showed that dormitory administrators at Pondok Modern Darussalam Gontor Campus 7 have a significant role in bullying preventive action. They act as instructors who provide an understanding of the dangers of bullying to new santri and as directors who supervise daily interactions in the dormitory. Through a personal approach, administrators can identify potential conflicts and deal with bullying before it develops. In addition, administrators also create programs that strengthen relationships between new students to prevent bullying. With a preventive and educative approach, the administrators hope to shape the character of students who are resilient, empathetic, and responsible, so as to create a harmonious dormitory environment free from bullying.